Enhancing EFL Vocabulary Mastery via Wordwall.net: A Mixed-Methods Study on Achievement and Student Challenges - Anjani, Nasywa Maudyna; Karim, Sayit Abdul; Radjaban, R.Y; Matas, Gordan; Winarna, Winarna (Jurnal Pendidikan Progresif, 2025)
Enhancing EFL Vocabulary Mastery via Wordwall.net: A Mixed-Methods Study on Achievement and Student Challenges. Objective: This study explores Wordwall.net, an online learning platform, to enhance students' English vocabulary and identify the challenges they encounter. Methods: This study employed a mixed-methods approach, involving twenty-five students from the Grade X Pharmacy Department at SMK YPKK 1 Sleman. The study aimed to gather quantitative data (pre-tests and post-tests) to measure vocabulary mastery, including spelling dictation, word translation, and collocation in sentences. Meanwhile, semi-structured interviews were conducted to gather qualitative data on the challenges of using the platform from six students, using purposive sampling. The data were analyzed using Miles & Huberman's interactive model, which includes data reduction, data display, and conclusion drawing. Findings: The results show a significant improvement in vocabulary mastery, with the average score increasing from 55.76 in the pre-test to 87 in the post-test. Moreover, Wordwall.net has the potential to enhance vocabulary and student engagement. However, students encountered challenges, including competitive pressure and unstable internet connections. Conclusion: These findings have significant implications for language teachers, school administrators, and curriculum developers, underscoring the importance of effectively integrating digital platforms. Additionally, policymakers should consider enhancing digital infrastructure in schools to ensure equitable access to online learning resources. The findings suggest that classroom teachers can effectively integrate Wordwall.net to enhance vocabulary mastery, boost motivation, and make learning more engaging. For institutions, this highlights the importance of providing digital infrastructure and training teachers in using web-based platforms. School administrators and policymakers should also support equitable access to reliable internet to ensure consistent learning outcomes. Keywords: challenge, vocabulary mastery, word wall, web-based learning.